UJI AKTIVITAS INSEKTISIDA BEBERAPA EKSTRAK TANAMAN PADA HAM A LIRIOMYZA SATIVAE (BLANCHARD) - Karolus A.N. Nainiti; I Wayan Supartha; IG.M.Oka Nurjaya (AGRICA, 2008)
The usage of herbal insecticide for leafminer control is based on the principle that organic compounds that are produced by plants to survive from the leafminer are selective, can be digested by the organism, and also can be broken down by heat, oxygen, and sunshine. This study was to test the activity of 15 plant extracts to find out which kinds of plant extracts had insecticide activity to Liriomyza Sativa. The study design was a randomized block design, with 17 treatments (15 kinds of plant extract and two controls), and was replicated five times. The trials were done at the glasshouse of Pest and Plant Disease Department of Agricultural Faculty at Udayana University. The results of the study showed that each plant extract that was used in this trial had different insecticide activity to L Sativa. The seed coat extract from the seed A. occidentale L. and the extract of P. retrofractum Vahl had the highest insecticide activity to L sativae.